2008
DOI: 10.1002/pssa.200824036
|View full text |Cite
|
Sign up to set email alerts
|

Effects of uniaxial stress on the magnetic properties of thin films and GMR sensors prepared on polyimide substrates

Abstract: The effects of externally applied uniaxial stress on the magnetic properties of Co thin films and pseudo‐spin‐valve (PSV) structures on flexible polyimide substrates were investigated. The advantage of the polyimide substrate is its flexibility and high elasticity (∼1%), which cannot be achieved using conventional crystalline substrates. The Co layers exhibit a macroscopic easy axis induced by the preparation process. When the stress is applied perpendicular to the induced in‐plane easy axis, the magnetic doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Although the supports used in these studies are considered rigid, they allow for a small amount of bending deformation, which is translated to the functional magnetic layers on the outer surface as a tensile deformation (bending strain) of the order of about 0.1%. Later, similar studies were performed using plastic polyimide substrates 106 , which allowed for magnetoelectric measurements at tensile strains of up to 0.75% directly applied by stretching 107 . Higher levels of deformation were obtained by Y.F.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Although the supports used in these studies are considered rigid, they allow for a small amount of bending deformation, which is translated to the functional magnetic layers on the outer surface as a tensile deformation (bending strain) of the order of about 0.1%. Later, similar studies were performed using plastic polyimide substrates 106 , which allowed for magnetoelectric measurements at tensile strains of up to 0.75% directly applied by stretching 107 . Higher levels of deformation were obtained by Y.F.…”
Section: State-of-the-artmentioning
confidence: 99%
“…21 Note also that the strain amplitude never exceeded 10 À3 , whereas in situ X-ray diffraction shows that similar films deform coherently with the substrate up to the much larger strain amplitude of 1%. 29…”
Section: Measurement and Control Of Strainmentioning
confidence: 99%
“…Later, similar studies were performed using plastic polyimide substrates, 106 which allowed for magnetoelectric measurements at tensile strains of up to 0.75% directly applied by stretching. 107 Higher levels of deformation were obtained by Chen et al, who deposited extended GMR films on buffer coated polyester transparency, as shown in Figure 5(a). 68 No performance degradation was observed in the magnetoresistive elements after 1000 bending cycles to a radius of about 22 mm.…”
Section: S Hmentioning
confidence: 79%